2017
DOI: 10.1097/pas.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Phosphaturic Mesenchymal Tumors

Abstract: Phosphaturic mesenchymal tumor (PMT) is a rare neoplasm of uncertain histogenesis that has been linked to tumor-induced osteomalacia (TIO) since 1959. The neoplastic cells produce increased amount of FGF23 which results in TIO via uncontrolled renal loss of phosphate (phosphaturia), and consequently diminished bone mineralization. To date, ∼300 cases have been reported. Although there is increasing evidence that PMT can be diagnosed by reproducible histopathologic features, firm diagnosis has been often restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 26 publications
2
42
0
5
Order By: Relevance
“…Here we present a detailed review of published English literature for TIO cases involving head and neck region ( n = 163) (5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, …”
Section: Discussionmentioning
confidence: 99%
“…Here we present a detailed review of published English literature for TIO cases involving head and neck region ( n = 163) (5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, …”
Section: Discussionmentioning
confidence: 99%
“…PMT could be seen in wherever the soft tissue and bone tissue is theoretically. The most common sites include extremities and acral sites but soft tissue organs like the liver or heart have not been reported to be involved yet [ 3 , 5 , 6 , 14 , 29 ]. Rarely PMTs present as multifocal disease [ [30] , [31] , [32] , [33] ].…”
Section: Clinical Description and Evaluationmentioning
confidence: 99%
“…Several studies have shown that mesenchymal tumors with morphological features of PMT and demonstrable levels of FGF-23 but without known TIO could occur [ 29 , 37 ]. Some referred to them as “non-phosphaturic” variant of PMT.…”
Section: Clinical Description and Evaluationmentioning
confidence: 99%
“…В Российской Федерации описания ФМО единичны [16][17][18][19]. Чаще всего ФМО обнаруживаются у пациентов среднего возраста [4,20], при этом самый ранний дебют заболевания описан у девятимесячного ребенка [21], гендерные различия не выявлены (М:Ж = 1,25:1 [22]).…”
unclassified
“…ФМО поражают мягкие ткани и кости любой локализации, однако наблюдается бóльшая тропность этих образований к мягким тканям конечностей и осевому скелету; крайне редко встречаются ФМО паренхиматозных органов и забрюшинной клетчатки [4,20,25], описан также случай мультифокального поражения [26]. В трубчатых костях ФМО чаще всего располагаются в эпифизах -до 82% [27]).…”
unclassified